Reevaluasi Konsep Pemilah Bahasa dan Dialek Untuk Bahasa Nusantara - Lauder, Multamia RMT (UI Scholars Hub, 2002)
Even today, there is disagreement among experts over how many languages and dialects there are in Indonesia. The methodological tools for classifying languages consist of mapping isoglosses, dialectometry, and measures of mutual intelligibility. The present article surveys the methodology used in N = 129 researches performed over the last 50 years and finds that researchers based their conclusions about languages and dialects predominantly on isoglosses while dialectometry and mutual intelligibility were much less used. It is also suggested that these three research methods be reevaluated in the light of the multilingual situation in Indonesia. We could possibly get better results with the isogloss method if we reconsidered the criteria for degree of sound similarity and the criteria for bundling isoglosses. For dialectometry, we should consider modifying the current percentages used to distinguish language-dialect divisions. For establishing mutual intelligibility, the factors that could be reassessed include techniques of testing, the procedures for choosing test-points and reference-points, and the criteria for choosing valid texts for testing.